Peningkatan perawatan diri pasien skizofrenia dengan teknik positive reinforcement - Arbita Wafdatul Ilmia (Universitas Muhammadiyah Malang, 2022)
Schizophrenia is a chronic mental disorder characterized by hallucinations, delusions, withdrawal from the social environment and failure of life functions. Self-care in schizophrenic patient becomes a serious problem and if it is left untreated, it will worsen the patient’s situation. This case study aimed to improve self-care of schizophrenic patient by utilizing the positive reinforcement. Psychological assessment used was interviews, observations, grafis test, wartegg, SPM, and WWQ. The intervention was given using a behaviour therapist with Skinner’s approach which consisted of 7 sessions. The subject was male, aged 31 years old. The intervention revealed a positive result, i.e., the subject became more active to take care of himself properly starting from brushing his teeth, watering all parts of his body, and wearing outfit properly.